'It's not quite right yet': Realism and Affect in A Woman under the Influence and A nos amours. Issue 2 (July 2017) - Kouvaros, George
Abstract : In The Antinomies of Realism Fredric Jameson positions realism as a discursive tension between two forms of temporality: on the one hand, the temporality of storytelling and the tale and, on the other, the temporality of affect. The outcome is a 'scenic present which in reality, but secretly, abhors the other temporalities which constitute the force of the tale or récit in the first place'. This article considers the usefulness of Jameson's diagnosis of realism for discussions of cinema. How are the temporalities that Jameson describes enacted in a medium much more directly invested in an experience of the present? The investigation of this question will occur in the context of a close engagement with two films in which the tension between storytelling and affect is evident at the level of the actors' performances: John Cassavetes's A Woman under the Influence (1974) and Maurice Pialat's A nos amours (1984).